How do we feed our livestock? Knowledge, perceptions and informational needs of the public and farmers in Germany - Hoffmann, Martina; Zupaniec, Milena; Lohmann, Mark; Böl, Gaby-Fleur; Pieper, Robert; Mader, Anneluise (Frontiers in Animal Science, 2024)
Little is known about knowledge and perceptions of the public and farmers on livestock feed. However, it is important to know their perspectives to find widely accepted and sustainable solutions in agriculture, which account for animal welfare, societal expectations, economy and the environment alike. Therefore, the objective of the present study was to assess knowledge, perceptions and informational needs regarding livestock feed among the general population and farmers. A Germanwide online survey was conducted with n = 1000 participants from the general population (representative for age and gender) and n = 251 farmers. Differences in answers were compared between the general population and farmers as well as between subgroups of the general population. Results indicate that the public is correctly informed about some livestock feeds, although knowledge gaps and misconceptions became evident. The general population rated potatoes, fodder beets, kitchen waste and bread as common feedstuffs for pigs, which was rather a common practice in smallholder "backyard" pig husbandry several decades ago. Ratings of relevant aspects of feed differ between the two groups and partially depend on sociodemographic variables (i.e. gender, rural/urban upbringing, age) in the general population. Farmers were more likely to have heard and know the meaning of the term feed additives and are better informed about the functions that are fulfilled by feed additives. Farmers also expressed higher agreement for use of most alternative feeds than participants from the general population, although no differences of acceptance levels were found for algae, insects, animal by-products and fungi. In the group of the general population, 56% agree with the use of cereals and only 17% with the use of soy as livestock feed. When asked for the level of knowledge on livestock feed, 42% of participants from the general population indicate low or very low knowledge, whereas 97% of farmers judged the knowledge among the public to be low or very low. Both groups rate the need for information on controls of feed highest. Providing more information on livestock feed to the public seems necessary to improve knowledge, increase acceptance of alternative feeds and of sustainable solutions in agriculture.